Continuous variation supports accommodating Lilium habaense and L. xanthellum within L. stewartianum (Liliaceae) - Gao, Yundong (Phytotaxa, 2015)
Continuous variation among Lilium stewartianum I.B.Balfour & W.W.Smith (1922: 127) and its close allies, L. habaense (1986: 51) and L. xanthellum F.T.Wang et Tang (1980: 283) have been observed by the author. In particular, L. habaense is distinguished from L. stewartianum on the basis of stamen having slightly shorter filaments (Wang et al. 1986). Lilium xanthellum is distinguished from the other two species by means of papillose nectaries that form two ridges along the bases of the inner tepals (Fig. 1) (Liang 1980). I have observed in the field that the variations in anthers length and nectary morphology are extensive, largely continuous, and dependent upon the phase of flowering. Therefore, on the basis of continuous variation I propose to accommodate L. habaense and L. xanthellum within L. stewartianum.